Two Decades of Research Into the Internationalization of Higher Education: Major Themes in the Journal of Studies in International Education (1997-2016). (May 2018) - Bedenlier, Svenja; Kondakci, Yasar; Zawacki-Richter, Olaf
In recent decades, internationalization within higher education has emerged as a distinct field for practice and research. However, there are few meta-analyses of how the research trends and foci of this topic have evolved and shifted over time. This article analyzes the content of the Journal of Studies in International Education ( JSIE ), a central outlet for internationalization research, thus shedding light on overarching developments and trends within the field. In this investigation, the text-mining tool Leximancer™ is used to generate concept maps based on the titles and abstracts of all 406 scientific articles published in the JSIE between 1997 and 2016 (first issue). Four major developmental waves in this research area are revealed: delineation of the field (1997-2001), institutionalization and management of internationalization (2002-2006), consequences of internationalization: student needs and support structures (2007-2011), and currently, moving from the institutional to the transnational context of internationalization (2012-2016). The results show how the meaning of the concept has evolved to encapsulate several other related concepts in research on higher education, while reporting practices toward internationalization at individual, institutional, and national levels.